Cult television - Gwenllian-Jones, Sara.; Pearson, Roberta E. (Minneapolis : University of Minnesota Press, 2004)
Leading scholars examine such shows as The X-Files; Star Trek; Xena, Warrior Princess; and Buffy the Vampire Slayer to determine the defining characteristics of cult television and map the contours of this phenomenon within the scope of popular culture.
Cult -- Toward a constructivist approach to media cults / Philippe Le Guern -- The mainstream, distinction, and cult TV / Mark Jancovich and Nathan Hunt -- Quality science fiction / Petra Kuppers -- Bright particular star / Roberta E. Pearson -- Fictions -- Virtual reality and cult television / Sara Gwenllian-Jones -- Charactor, or, The strange case of Uma Peel / David A. Black -- Flexing those anthropological muscles / Karen Backstein -- Monsters and metaphors / Mary Hammond -- Fans -- How to tell the difference between production and consumption / Alan McKee -- Trainspotting The Avengers / Toby Miller -- Star Trek, Heaven's Gate, and textual transcendence / Jeffrey Sconce -- A kind of German Star Trek / Eva Vieth.
Includes bibliographical references.
Print version record.
English.
JSTOR
Keywords: Television programs; Fiction television programs; Fictions télévisées.; Émissions télévisées.; television programs; PERFORMING ARTS -- Television -- Reference; PERFORMING ARTS -- Television -- History & Criticism; Fiction television programs; Television programs; Televisieseries; Televisiespelen; Cultfilms